Oblikovanje, razvoj in vodenje timov - Marič, Miha; Lambić, Ana; Vukovič, Goran (University of Maribor Press, 2020)
Designing, Developing and Leading Teams. Today, various forms of teamwork can be found in just about every event, both in private and professional life. It is important to be aware of the necessity and importance of the work of individuals in groups or teams, as a functional unit, because as a result we achieve better, more efficient and more successful work. An individual always treats himself according to his relationship to other individuals or groups. This can be projected on the functioning and work of employees in organizations. Working in teams connects the quality of mutual cooperation of those who manage and execute business processes. Teamwork is an indispensable work standard within organizations, as it mitigates the fluctuations of the effects of individuals (team members) and significantly contributes to the consistency of the work performed; therefore, success is often based on team orientation.